The higher you go the less you will know: placing camera traps high to avoid theft will affect detection. Issue 4 (26th September 2016) - Meek, Paul D.; Ballard, Guy A.; Falzon, Greg
Abstract: Vandalism and theft of camera traps is common, imposing financial and data losses on wildlife professionals. Like many 'victims', our response to a spate of thefts was to attempt to install camera traps at heights we suspected would reduce detection and interference by vandals. We sought to determine if placing camera traps above humans' eye line, to reduce the likelihood of detection and theft by vandals, would compromise predator detection in road‐based surveys. Our efforts to resolve this problem led us to discover the importance of placing camera traps at a height commensurate with the height of the animals being studied. Monitoring stations comprised of two camera traps, one at 0.9 m and another at 3 m above ground level, were established at regular intervals along trails during two survey periods. We also conducted a pilot trial to compare vertical (facing downwards) to horizontal (facing across) orientation of camera traps to detect medium‐sized mammals. We compared images recorded by the pairs of camera to consider whether height made a significant difference to detections of predators. We found that cameras placed 3 m high and those facing downwards reduced the detection rate of all species compared to those at 0.9 m, so placing camera traps higher than normal significantly compromised our survey data. It is important to note that such data loss would not necessarily be apparent without a robust comparison between deployment strategies. Saving camera traps but concurrently sacrificing data quality is unlikely to be an acceptable outcome for many wildlife professionals. This study reports that placing camera traps too high will reduce the detection of animals and compromise the quality of the survey data. Abstract : Vandalism and theft of camera traps is common, and may be reduced by placing camera traps high above the human eye line. However, the optimal placement of camera traps for detecting wildlife is dependent on many variables related to the landscape, environmental conditions and target species. Our research found that camera trap height is important in optimizing detection rates of wildlife species, and placing camera traps too high will reduce the detection of animals and compromise the quality of the survey data.